Gender Differences in Ethics Research: The Importance of Controlling for the Social Desirability Response Bias - Dalton, Derek; Ortegren, Marc (2011)
Gender is one of the most frequently studied variables within the ethics literature. In prior studies that find gender differences, females consistently report more ethical responses than males. However, prior research also indicates that females are more prone to responding in a socially desirable fashion. Consequently, it is uncertain whether gender differences in ethical decision-making exist because females are more ethical or perhaps because females are more prone to the social desirability response bias. Using a sample of 30 scenarios from prior studies that find gender differences, we examine whether these gender differences remain robust once social desirability is controlled for in the analysis. Our data suggest that the effect of gender on ethical decision-making is largely attenuated once social desirability is included in the analysis. In essence, the social desirability response bias appears to be driving a significant portion of the relationship between gender and ethical decision-making. We discuss several important research implications of this study.
Keywords: ethics research; social desirability response bias; Gender